Solid-state electrodes and sensors
Patent Information
- Application Number
- JP2024030236
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2014-06-11
- Filing Date
- 2024-02-29
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2035-06-11
Smart Images

Figure 0007610053000017 
Figure 0007610053000018 
Figure 0007610053000019
Abstract
Description
[Technical field]
[0001] The present invention provides solid-state electrodes for use in electrochemical analyses, including pH measurements, comprising an "indicator electrode" ("IE") utilizing a redox-active analyte insensitive material ("AIM"), and a working electrode ("WE") utilizing a redox-active analyte sensitive material ("ASM"), as well as methods for making and using the materials of the invention, and electrodes, sensors, and devices comprising same. In one embodiment, the AIM is incorporated into the IE in conjunction with a pseudo reference electrode ("PRE") and an ASM that functions as a WE. The IE corrects for drift in the pH reading (or other analyte measurement) caused by changes in the PRE potential, thereby improving the accuracy of the measurement and eliminating the need for a calibration process required for other types of analyte sensors. The present invention thus relates in particular to the fields of chemistry and electrochemistry, and to the fields of analyte measurements, particularly pH measurements, and all of the various fields in which such measurements are made. [Background technology]
[0002] Electrodes and analyte sensing devices based on AIM and / or ASM electrochemistry have been previously described, see U.S. Patent Nos. 4,857,167, 5,223,117, 7,901,555, 8,177,958, 8,197,650, 8,506,779, 8,562,797, 8,877,037, 8,956,519, and 8,961,754 (Patent Documents 1 to 10), which are incorporated herein by reference. See also PCT Publication Nos. 2010 / 026842, 2010 / 028726, 2011 / 045385, 2013 / 112767, and 2013 / 134582, and 2014 / 106066 (Patent Documents 11 to 16), each of which is incorporated herein by reference. Electrodes utilizing AIM ferrocene are described in Lafitte et al. (2008), Electrochemistry Communications, 10(12), 1831-1834; Hickman et al. (1991), Science, 252(5006), 688-691; Robinson and Lawrence (2006), Electroanalysis, 18(2006) 677-683; and Robinson and Lawrence (2008), Analytical Sciences 24.339-343. Ferrocene hydrogels have been previously described in the art, but these techniques and materials are limited to their use as redox mediators for the purpose of transducing signals from separate sensing elements. Furthermore, these references do not teach or contemplate the physical properties of ferrocene hydrogels discussed herein. Furthermore, the present invention provides ferrocene hydrogel pH sensing elements that detect and report a reference redox signal.
[0003] Electrochemical sensors utilizing ASM / AIM and square wave voltammetry (SWV), sometimes called "voltammetric sensors", have been hailed as offering the opportunity for "calibration-free" sensing (meaning that the sensor does not require calibration by the end user), especially for pH measurements. In these sensors, a pH-sensitive signal generated by a WE and a pH-insensitive signal generated by an IE are simultaneously generated for a given analyte using the SWV method. When the analyte is hydronium ion (for pH measurements), the ASM WE changes potential in response to changes in hydronium ion concentration, whereas an ideal AIM for an IE in a pH meter would generate a constant potential regardless of changes in pH. Both of these potentials are measured against a reference electrode (RE) potential, as shown in FIG. 1. In this way, the difference between the ASM and AIM signals can be correlated to pH or other analytes, and ideally this difference is independent of the absolute potential of the RE, which can be either a traditional reference electrode ("CRE") or a PRE. Thus, for a voltammetric sensor, changes in the RE have much less impact on the results than for a conventional potentiometric pH sensor that relies entirely on the stability and accuracy of the RE. Indeed, a simpler PRE (e.g., a solid Ag / AgCl composition) may be used for a voltammetric sensor instead of a CRE (such as Ag / AgCl or mercurous chloride CRE trapped in the reference solution). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] U.S. Patent No. 4,857,167 [Patent Document 2] U.S. Patent No. 5,223,117 [Patent Document 3] U.S. Patent No. 7,901,555 [Patent Document 4] U.S. Patent No. 8,177,958 [Patent Document 5] U.S. Patent No. 8,197,650 [Patent Document 6] U.S. Patent No. 8,506,779 [Patent Document 7] U.S. Patent No. 8,562,797 [Patent Document 8] U.S. Patent No. 8,877,037 [Patent Document 9] U.S. Patent No. 8,956,519 [Patent Document 10] U.S. Patent No. 8,961,754 [Patent Document 11] International Publication No. 2010 / 026842 [Patent Document 12] International Publication No. 2010 / 028726 [Patent Document 13] International Publication No. 2011 / 045385 [Patent Document 14] International Publication No. 2013 / 112767 [Patent Document 15] International Publication No. 2013 / 134582 [Patent Document 16] International Publication No. 2014 / 106066 [Non-patent literature]
[0005] [Non-Patent Document 1] Lafitte et al. (2008), Electrochemistry Communications, 10(12), 1831~1834 [Non-Patent Document 2] Hickman et al. (1991), Science, 252 (5006), 688~691, Robinson and Lawrence (2006), Electroanalysis, 18 (2006) 677~683 [Non-Patent Document 3] Robinson and Lawrence(2008),Analytical Sciences 24.339~343 Summary of the Invention [Problem to be solved by the invention]
[0006] However, there is still a need for calibration-free sensor technology, since none of the so-called "calibration-free" sensors have been proven to be so in practice and / or exhibit deficiencies in accuracy, signal strength, and / or durability. For example, previous self-calibrating sensors using ferrocene (Fc) as an internal reference electrode have poor stability over time, and Fc is sufficiently pH-insensitive only over a limited pH range. Any pH sensitivity reduces the accuracy of any required calibration, limiting the reliability of the test results.
[0007] In terms of sensitivity, the prior art AIM electrodes (IEs) based on Fc typically exhibit weaker and relatively noisy signals. In addition, the prior art IEs and WEs generate relatively weak and / or unstable signals, especially under stringent test conditions. Therefore, there remains a need for improved materials and methods for detecting analytes using ASM-based WEs and AIM-based IEs. The present invention meets this need. [Means for solving the problem]
[0008] It is a first object of the present invention to provide new and useful components of a pH meter including a WE and an IE, as well as a complete sensor that can be used to measure pH under a wide variety of conditions not previously possible with prior art techniques and devices. In a preferred embodiment, the pH sensor of the present invention is a small, compact, solid-state sensor that is wet-dry reversible and comprises an AIM-based IE, in which the ASM of the WE and the AIM of the IE are incorporated into a crosslinked hydrogel matrix that is non-covalently bonded to a conductive substrate such as carbon, doped silicon, modified silicon, or conductive silicon derivatives, or a conductive polymer material.
[0009] In a first aspect, the present invention provides a material suitable for use as an AIM. In one embodiment, the material is a preparation of polymerizable monomers suitable for use in forming a hydrophilic cross-linked gel comprising an AIM. In another embodiment, the material is a hydrophilic cross-linked gel comprising an AIM. In another embodiment, the material is a preparation of polymerizable monomers that form a solid buffer that is coated onto the ASM that acts as the AIM.
[0010] In a second aspect, the invention provides an electrode comprising a porous conductive substrate to which is non-covalently bound a hydrophilic cross-linked hydrogel comprising an AIM or ASM. In one embodiment, the electrode is an indicator electrode (IE). In another embodiment, the electrode is a WE. In another embodiment, the electrode is a solid-state alternative to the traditional glass probe of a pH meter.
[0011] In a third aspect, the present invention provides an analyte sensing device comprising an IE comprised of a hydrophilic cross-linked hydrogel containing an AIM, a working electrode (WE) containing an ASM, and a RE, said gel non-covalently bound to a porous conductive substrate. In one embodiment, the RE is a solid PRE such as a solid mixture of silver and silver chloride (Ag / AgCl) or a chlorided silver surface. In one embodiment of the device, the ASM of the WE is similarly covalently bound to or stably encapsulated within the hydrogel, which in turn is non-covalently bound to the conductive substrate to form the WE. The conductive substrate may be porous or may be shaped or treated to facilitate attachment of the hydrogel matrix.
[0012] In a fourth aspect, the invention provides a method for measuring electrode potentials from an ASM-containing WE and an AIM-containing IE relative to a RE, such as a solid PRE, and establishing a correlation between the analyte concentration or level and the difference between the WE potential and the IE potential. In one embodiment, the correlation is used to derive the pH of the analyte sample.
[0013] In one embodiment, the present invention relates to an improvement in a process for measuring an analyte using an analyte sensor, the analyte sensor comprising a first WE, an IE, a counter electrode ("CE"), a RE which may be a CRE or a PRE, means for applying a square wave potential sweep between a first pair and a second pair of electrodes, and means for detecting a relative shift between a first peak and a second peak in a square wave voltammogram, the first WE comprising a first set of redox species (ASM), and the first set of redox species is a PRE. the IE comprises one or more redox species that are sensitive to the analyte; the IE comprises a second set of redox species (AIMs), the second set of redox species comprises one or more redox species that are insensitive to the analyte; the first pair of electrodes comprises a first WE and RE, and the second pair of electrodes comprises an IE and RE; the first peak is generated by one of oxidation and reduction of the first set of redox species and the second peak is generated by one of oxidation and reduction of the second set of redox species; The improvement includes the use of an IE, where the second set of redox-active species is not covalently bound to the surface of the IE, but is instead encapsulated in a polymeric material that is covalently, non-covalently, or both bound to the surface of the IE. In another embodiment, the improvement includes the use of a WE, where the first set of redox-active species is not covalently bound to the surface of the WE, but is instead encapsulated in a polymeric material that is covalently, non-covalently, or both bound to the surface of the WE. In another embodiment, the invention provides a device comprising both an improved IE and an improved WE. [Brief description of the drawings]
[0014] [Figure 1]Schematic diagram of how any drift in RE potential in an uncompensated voltammetric sensor results in measurement error for an otherwise stable WE that includes an analyte-sensitive material (ASM) (illustrated in A of the figure). This measurement error cannot be distinguished from changes in analyte concentration. If an analyte-insensitive material (AIM) is used as an additional IE (illustrated in B of the figure), any apparent drift must be attributed to the RE. Thus, the drift in IE potential can be used to offset the observed drift error at the working electrode (illustrated in C of the figure). In this way, the difference between the WE and IE potentials is effectively decoupled from changes in the properties or characteristics of the RE, and the sensor provides a more accurate measurement of the analyte. [Diagram 2] Figure 1 shows data demonstrating that ferrocene-methanol (Fc-MeOH) exhibits virtually the same square wave peak potential in buffer solutions from pH 1 to pH 10. To generate this data, buffer solutions containing 1 mM Fc-MeOH and 100 mM sodium chloride were each scanned five times. Error bars reflect standard deviation. It is an object of the present invention to provide a ferrocene hydrogel for use in IE. [Diagram 3] The components for the calibration-free solid-state pH sensor of the present invention are shown and are more specifically described in Example 1. The ASM is located at the WE, while the AIM is located at the IE. Carbon fiber composite is used as the substrate for both electrodes. The counter electrode (CE) in this embodiment is a metal (e.g., stainless steel) ring that surrounds the WE. All voltammetric measurements are performed against a pseudo reference electrode (PRE) in this example. [Figure 4] 1 shows the effect of pH change on the pH peak of the WE (ie, ASM) versus the peak of the IE (AIM, eg, Fc) for a pH sensor comprising an AIM hydrogel of the invention, as described in Example 1. [Diagram 5] The effect of altering the RE on the WE-IE pair of the present invention is shown as described in Example 1. The results demonstrate that the WE-IE relationship is independent of the CRE. [Figure 6] As described in Example 2, calibration of the WE-IE pair in an all-solid-state sensor system is shown. [Figure 7] 1 shows the results of comparing the WE-IE couple with a conventional glass pH electrode, as described in Example 3. [Figure 8] 1 illustrates various electrode configurations for a sensor (device) of the present invention. [Figure 9] 1 shows a multi-layer plate incorporating a pH sensor of the present invention. [Figure 10] 1 shows details of a pH sensor designed for measuring microliter samples according to an exemplary embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Prior art AIM-based indicator electrodes and ASM-based working electrodes generally exhibit limited accuracy, poor stability, and narrow pH insensitive range for AIM IE and narrow pH sensitivity for ASM WE. The AIM moiety (e.g., ferrocene) in these prior art electrodes is typically directly bound to the substrate surface by covalent bonds. For electrodes in which AIM or ASM is covalently bound to the substrate surface, the effective achievable AIM or ASM concentration is limited by the two-dimensional surface area of the substrate accessible for reaction / binding. The achievable functional group density is also usually below the density of reaction sites, which results in low signal levels and resulting uncertainty in electrode potential measurements.
[0016] Furthermore, previous attempts to provide a completely solid-state wet-dry reversible pH sensor have not led to a commercial product, and prior to the present invention, no solid-state pH meters based on AIM / ASM solid-state technology are commercially available. The failure of previous attempts may be due to an inability to generate sufficient signal strength in the WE, too rapid signal degradation during use or storage, insufficient sensitivity over a sufficiently wide pH range, and insufficient robustness to analyte samples or other use conditions. The present invention provides various materials, methods, electrodes, sensors, and devices that overcome these limitations by first providing a hydrogel material in which the ASM or AIM is covalently bonded to or stably encapsulated within a crosslinked hydrophilic polymer matrix, referred to as a "hydrogel polymer matrix" or "hydrogel."
[0017] Hydrogel Polymer Matrix In the IEs and WEs of the present invention, the AIMs, which may be or include ferrocene derivatives, and the ASMs, which may be or include anthraquinone derivatives, are covalently linked to or physically encapsulated within a highly swollen crosslinked hydrophilic polymer matrix ("hydrogel") that is not covalently linked to the conductive substrate but is attached thereto by non-covalent bonds. The three-dimensional hydrogel structure accommodates much higher concentrations of AIMs (or ASMs) than have been achieved in the prior art. The high water permeability of the hydrogel ensures rapid interaction between the AIMs (or ASMs) and the sample being tested for analyte concentration, facilitating rapid response to changes in the sample. The AIM and ASM hydrogels of the present invention also exhibit good wet-dry reversibility, retaining physical integrity when dried and rapidly restoring redox activity upon rewetting. The pH insensitive range of the pH sensors of the present invention typically encompasses at least pH 2 to pH 10.
[0018] Ferrocene (Fc) has been described as a suitable AIM for use in IE, but immobilization of high concentrations of ferrocene often leads to a small but significant pH sensitivity that falls outside a narrow pH range. As a result, the analyte-dependent properties of the AIM are only partially realized. For example, physical immobilization of polyvinylferrocene (an AIM with an inherently high functional group density) onto a substrate generates a low-resolution signal.
[0019] The present invention arose in part from the discovery that the pH insensitivity range of certain ferrocene derivatives is considerably broader in solution than in the solid state. For example, ferrocenemethanol (Fc-MeOH, MW=216) exhibits virtually the same square wave peak potential in buffer solutions from pH 1 to 10, as shown in Figure 2. Thus, one object of the present invention is to preserve the inherent pH insensitivity of AIMs, and the inherent pH sensitivity of ASMs, in solid-state electrode and sensor embodiments.
[0020] The materials provided by the present invention provide an AIM operating environment at the molecular level that mimics that of the AIM in free solution. The general approach of the present invention is to incorporate the Fc derivative into a hydrated polymer matrix. The resulting polymer is then disposed on a conductive substrate to form an electrode. Preferably, the Fc derivative is covalently bound to a hydrogel, defined as a cross-linked polymer matrix that is highly swollen by water but not water-soluble. Typical hydrogels for use according to the present invention using Fc and Fc derivatives have equilibrium water content curves that are significantly higher than the mass function of the polymer. In contrast, polymers such as polyvinyl alcohol (suitable for use in forming the WE of the present invention) that have been rendered insoluble by thermal or chemical cross-linking have water mass functions that are comparable to or significantly less than the mass function of the polymer. These are less suitable as host polymers for Fc, except where a lower pH-insensitive range is acceptable.
[0021] For the present invention, suitable hydrogels are formulated as multi-component systems, which include one or more comonomers that form a three-dimensional network of polymer chains that can hold water in the spaces between the chains. To form the AIM of the present invention, in one embodiment, at least one of the comonomers is a reactive Fc derivative, such as vinylferrocene. Vinylferrocene (MW=212) is a reactive analog of Fc-MeOH, but is insoluble in water. However, it can be used in accordance with the present invention with other hydrophilic vinyl comonomers and crosslinkers to form hydrogels based on polyacrylates, polyacrylamides, their polyether derivatives, and many others known in the art. Formulating vinylferrocene as the minor component and other hydrophilic comonomers as the major component serves to solvate vinylferrocene and provide it with a favorable hydration environment to preserve its pH insensitivity. In a preferred embodiment, the AIM hydrogel is formulated such that 80% of the swollen gel mass is water. In some embodiments, the AIM hydrogel is formulated such that 85-95% of the swollen gel mass is water.
[0022] The composition of the AIM-containing hydrogel, whether it is dry or wettable, can be described in terms of the polymer matrix. The present invention integrates two properties of the matrix that affect AIM performance: the mole percent (or mole %) of AIM units as a percentage of total polymer units, and the mole % of crosslinker as a percentage of total polymer units. For the purposes of the present invention, a monomer is considered to be a molecule with a pendant polymerizable group. A crosslinker is a molecule with two polymerizable groups. Both the AIM mole % and the crosslinker mole % are determined by the stoichiometric amounts of monomers used, assuming that the polymerization reaction proceeds to completion and all monomers are incorporated into the polymer chain.
[0023] In one embodiment of the present invention, the mole % of AIM in the polymer matrix is kept at 0.1-1. The degree of crosslinking is 1-2 mole % crosslinker based on total comonomer. Both of these variables affect the electrochemical performance. If the Fc units in the hydrogel are not sufficiently hydrated, the redox properties will be more similar to those of insoluble ferrocene materials. This can occur if the ferrocene content is greater than 0.5-1 mole % of the matrix, or if the crosslink density is greater than 1.5-2 mole %. If the ferrocene content is less than 0.1-0.2 mole %, the ferrocene density will not be sufficient to give a strong redox signal. If the crosslink density is less than 0.8-1 mole %, the hydrogel will lack physical integrity and will separate from the substrate or gradually disintegrate.
[0024] In some examples, the mole % of AIM in the polymer matrix is kept at 0.1-1.5. The degree of crosslinking is 1-2 mole % crosslinker based on total comonomer. The resulting hydrogel exhibits good structural integrity and bond strength with the surface of the electrode through non-covalent bonds. In some examples, this type of embodiment is resistant to gamma irradiation treatment, as it may be required to sterilize the sensor for use in the biochemical, pharmaceutical, and food processing industries.
[0025] In other embodiments, hydrophilic derivatives of ferrocene monomers may be used to provide good solvation at greater than 1 mol% ferrocene in the polymer chain. Similarly, bulky Fc monomers may be used to prevent aggregation and aid in solvation.
[0026] Thus, in some embodiments, the materials for making IEs provided herein include AIMs covalently linked to a hydrophilic polymer matrix (or to monomers that can be used to form such a matrix). Once the matrix is crosslinked as described herein, it is referred to as a "hydrogel." Thus, the materials provided herein include "AIM polymers," "AIM hydrogels," "AIM monomers," and various other monomers for their preparation. In one embodiment, the AIM hydrogels of the present invention include ferrocene in a crosslinked hydrophilic polymer. In one embodiment, the AIM hydrogels are formed by copolymerizing vinyl ferrocene with one or more hydrophilic comonomers, at least one of which is difunctional or multifunctional. The difunctional or multifunctional comonomers are capable of forming crosslinks upon polymerization and are referred to herein as crosslinkers. Copolymerization of these components results in a hydrogel that provides an IE that exhibits a pH-insensitive signal under SWV operating conditions. This signal is then used along with a pH-dependent signal from the ASM WE as described above to generate a signal corresponding to an analyte concentration, in one embodiment, pH, according to the methods described herein.
[0027] In a preferred embodiment, the AIM hydrogel comprises a polymer formed from the radical polymerization of N,N-dimethylacrylamide (97-99 mol%), poly(ethylene glycol) diacrylate (1-2 mol%), and vinylferrocene (0.1-1.5 mol%).
[0028] In another embodiment, the Fc monomer can be used as a linear homopolymer without a crosslinker. As mentioned above, vinylferrocene is not hydrophilic enough to be a preferred embodiment. However, Fc derivatives such as those illustrated in structure Fc-II in Table 1 below can be prepared according to the present invention using a suitable hydrophilic linker between Fc and the polymerizable group to increase the overall hydrophilicity.
[0029] In another embodiment, multifunctional Fc monomers containing two or more polymerizable groups, such as those illustrated in structure Fc-III in Table 1 below, may be used alone to provide crosslinked homopolymers. In this case, each repeat unit of the polymer contains an Fc group, which results in exceptionally high Fc functionality, but may provide increased pH sensitivity for some applications. By introducing a hydrophilic comonomer as a linker, as in some embodiments of the present invention, the Fc functionality is "diluted" and the resulting copolymer exhibits enhanced hydrophilicity.
[0030] In another embodiment, the AIM hydrogel is a linear copolymer containing an AIM monomer and one or more monofunctional comonomers, as illustrated in structures Linear Polymers 1 and 2 in Table 3 below. The comonomers can be hydrophilic with pendant groups that aid in solvation of the AIM, as illustrated in Linear Polymer 2. The linear polymers should be large enough (greater than 50-100 monomer units per chain) to prevent leaching from the electrode substrate on which the AIM hydrogel is disposed.
[0031] In another embodiment, the AIM hydrogel comprises AIM molecules physically encapsulated in a crosslinked polymer matrix. Suitable AIM molecules may be linear polymers of 50-10,000 units in length, such as those illustrated in the structure of Linear Polymer 1, or may be oligomers or dendrimers, as illustrated in the structures shown in Table 4 below. Such structures, called interpenetrating networks (IPNs), allow any AIM molecule to be encapsulated in a crosslinked polymer without the need for polymerizable groups on the AIM. The components of an IPN are generally not covalently bonded to each other.
[0032] For this embodiment, preferred polymerizable groups are those that undergo radical polymerization, including vinyl, acrylamide, methacrylamide, acrylate, and methacrylate groups. These have the advantage of providing alkyl polymer chains that are chemically robust and stable to hydrolysis. The molecule itself may contain hydrophilic groups, such as alcohol or ethylene glycol groups, or AIM moieties that include ferrocene.
[0033] In another embodiment, polymerizable groups include those that react by amide or ester bond formation, including monomers that contain both a reactive carbonyl (such as an acid chloride) and a nucleophile (such as an alcohol or amine group), which result in polyester or polyamide polymer chains.
[0034] In another embodiment, the hydrogel comprises a non-covalently crosslinked hydrogel, also known as a supramolecular hydrogel, which is usually composed of amphiphilic colloidal components. This embodiment is considered less preferred as supramolecular hydrogels are generally less robust to heat and solvent dissolution.
[0035] [Table 1]
[0036] Exemplary ferrocene-containing monomers are shown in Table 1. One example used in preferred embodiments is vinylferrocene (Fc-I), where the polymerizable group is linked directly to the ferrocene aromatic ring. Another example, illustrated in structure Fc-II, features an acrylate (X=oxygen) or acrylamide (X=nitrogen) polymerizable group connected by a methylene linker. The linker is C n H 2nwhere n can be 1-6. The linker can also contain hydrophilic groups such as ethylene glycol units. The alkene portion of the polymerizable group can be either acrylic (as shown) or methacrylic, where a methyl group is attached to the carbon alpha to the carbonyl group. These different derivatives can be desirable for their rate of polymerization and resistance to hydrolysis. Hydrolysis of the pendant AIM moieties on the polymer chain contributes to signal attenuation. Another type of AIM monomer is one that contains two or more polymerizable groups, illustrated in structure Fc-III above. Such structures provide crosslinking in the polymer and can be used alone or as copolymers with other monomers. AIM polymers and AIM hydrogels can be based on any hydrophilic polymer matrix. Vinyl polymers are particularly suitable because a wide variety of properties can be obtained by controlling the identity and combination of monomers, comonomers, and crosslinkers. Crosslinking offers the advantage that the polymer can be polymerized in-situ, thereby forming a robust network that is physically bound to the substrate and, optionally, penetrates the substrate with some degree of porosity. Various levels of anionic, cationic, or zwitterionic character can be introduced into the hydrogel by incorporating monomers with these attributes. Suitable monomers include those listed below in Tables 2 and 3. Although ferrocene hydrogels are referred to below, other AIMs such as organometallic, ionic salts, and redox-active organic species can also be formed into the hydrogel using these monomers.
[0037] For example, viologen polymers are well known as robust hydrophilic polyelectrolyte structures with two reversible redox peaks (Naoki et al. "Polyviologen Hydrogel with High-Rate Capability for Anodes toward an Aqueous Electrolyte-Type and Organic-Based Rechargeable Device." ACS Applied Materials & Interfaces 5.4 (2013): 1355-1361). Metal salts traditionally used as redox markers, such as ferricyanide, can also be incorporated into polymers according to the present invention by substituting one of the ligands with a polymerizable group.
[0038] [Table 2]
[0039] Exemplary radically initiated monomers are shown in Table 2. Structures I and II are monomers known to be amphiphilic, capable of solvating hydrophobic molecules and also imparting hydrophilic properties to hydrogels. These structures contain an alkene group that participates in radical chain polymerization, resulting in an alkyl polymer chain with the indicated pendant group. The pendant group can be selected to impart hydrophilic properties to the polymer.
[0040] Structures III and IV are bifunctional monomers used for crosslinking in hydrogels. In structure IV, the spacer group may contain 1-10 ethylene glycol units in preferred embodiments, or 20-1000 ethylene glycol units in other embodiments. Longer spacers may affect the swelling of the crosslinked hydrogel depending on the bulk properties of the poly(ethylene glycol) chain used.
[0041] [Table 3]
[0042] Two exemplary ionic monomers are shown in Table 3. These monomers can increase the hydrophilicity of the AIM polymer beyond that achievable with non-ionic monomers.
[0043] A wide range of polymer / hydrogel properties can be obtained by varying the choice of comonomer and / or crosslinker, the ratio of these components, and the total solids content of the hydrogel. Solids content refers to the percentage of gel absorbed by the polymer matrix compared to water. A typical hydrogel contains 1-10% solids, which can be highly dependent on the ability of the material to absorb water and swell. This swelling itself is highly dependent on the degree of crosslinking. In some embodiments of the present invention, the AIM polymer or AIM hydrogel incorporates vinylferrocene (or other suitable ferrocene derivatives or other AIM-linked monomers or polymers, or mixed preparations of AIM and monomer(s)) throughout the three-dimensional polymer structure, allowing for a much larger effective population of AIMs than previously achievable without exceeding a threshold density of ferrocene (or other AIM) groups, resulting in a narrower pH-insensitive range than desired.
[0044] Representative polymers prepared using the methods of the present invention are shown in Tables 4 and 5. These polymers include linear polymers containing vinylferrocene and the comonomers N,N-dimethylacrylamide (II) or the more hydrophilic triethylene glycol methyl ether methacrylate (I) or diethylene glycol methyl ether methacrylate (similar to I except that n=2), as well as ferrocene-containing hydrogels crosslinked with poly(ethylene glycol) diacrylate (IV) or methylene(bis)acrylamide (III). In Tables 4 and 5, x, y, and z refer to the stoichiometric ratio of the respective monomers. For example, the ratio of x:y corresponds to the degree of ferrocene (or other AIM) substitution of the host polymer (e.g., 0.1 for 1 mole % ferrocene as discussed above).
[0045] [Table 4]
[0046] Table 4 shows examples of linear polymers incorporating Fc as an AIM. The values x, y, and z indicate the stoichiometric ratio of monomer units randomly distributed throughout the polymer. In a preferred embodiment illustrated with Linear Polymer 1, the ratio of x and y can be 100:1 to 1000:1. In a preferred embodiment illustrated with Linear Polymer 2, the ratio of x, y, and z can be 90:1:10, 85:1:15, 80:1:20, 900:1:100, 800:1:200, and 0:1:100. In other embodiments, block copolymers can be used to know the exact placement and distribution of groups of monomer chains.
[0047] Linear polymers 1 and 2 illustrate methods and materials for the incorporation of Fc (for illustration purposes only; any AIM can be used) functionality into hydrophilic polymers. The use of three comonomers in linear polymer 2 provides control over hydrophilicity and other physical properties. However, both linear polymers dissolve in water over time. Thus, crosslinking may be used in accordance with the present invention to delay or eliminate dissolution.
[0048] Crosslinked polymers 1 and 2 incorporated crosslinkers III and IV, respectively, as shown in Table 5, where the crosslinkers are highlighted in bold.
[0049] [Table 5]
[0050] Table 5 shows examples of crosslinked polymers incorporating Fc as an AIM. The values x, y, and z indicate the stoichiometric ratio of monomer units randomly distributed throughout the polymer. For crosslinked polymer 2, it may be preferable to modify the bifunctional crosslinker to contain amide linkages, which are more robust to hydrolysis, rather than ester linkages. In preferred embodiments, for crosslinked polymers such as those shown, the ratio of x, y, and z may be 1000:1:5 to 1000:1:20, 1000:10:5 to 1000:10:20. In other embodiments, the polymer is composed exclusively of AIM and crosslinker monomers in a ratio of 0:1:1000 to 0:20:1000.
[0051] In some embodiments, polyvinyl alcohol is functionalized with ferrocene and a linear polymer of the present invention (e.g., a linear polymer containing acetyl groups, ferrocene, and hydroxyl groups) that is crosslinked by either thermal, chemical, or radiation. For example, in one example, the crosslinker is selected from the group consisting of maleic anhydride, maleic acid, glutaraldehyde, diisocyanate, divinyl ether, periodate, or any common dialdehyde, as disclosed in http: / / ntrs.nasa.gov / archive / nasa / casi.ntrs.nasa.gov / 19790012957.pdf, the disclosure of which is incorporated herein in its entirety. In some examples, PVA is functionalized with ferrocene derivatives with either long or short side chains, and / or electron-withdrawing or electron-donating groups that favor tuning the peak potential to a more positive or more negative potential depending on the application. In some embodiments, certain ferrocene derivatives are selected to be more robust and resistant to scan-dependent decay, as disclosed at http: / / www.ncbi.nlm.nih.gov / pmc / articles / PMC2975373 / table / T1 / , which is incorporated herein in its entirety.
[0052] Those skilled in the art will appreciate that the present invention provides monomers, polymers, and hydrogels useful for making WEs and WEs formed therewith that differ from the AIM materials described above only in that the AIM is replaced by ASM. Thus, the electrochemically active components of the hydrogels of the present invention may include either analyte-insensitive materials, analyte-sensitive materials, or both. For example, vinyl anthracene or 2-acrylamido-anthraquinone (shown below in Table 6) may be incorporated into the hydrogel matrix described above to form the ASM hydrogels of the present invention. Alternatively, both ASM and AIM vinyl monomers may be used as comonomers in the same hydrogel that exhibit both analyte-sensitive and analyte-insensitive responses.
[0053] [Table 6]
[0054] In various embodiments of the electrodes, sensors, and devices of the present invention, polyacrylamide-ferrocene complexes and polyacrylamide-anthraquinone complexes are used as AIMs and ASMs, respectively. Such embodiments include two linear polymers or copolymers, where both the ASM and the AIM are incorporated as comonomers into the polymer matrix to provide a random copolymer of the desired composition. Such embodiments also include those in which the WE and IE are on separate substrates.
[0055] In some embodiments, AIMs such as ferrocene derivatives already in oligomeric, polymeric, or dendrimeric form are used to prepare AIM hydrogels in which the AIMs are not covalently bound to the hydrogel but are retained therein by physical encapsulation. Effective physical encapsulation requires that the effective network density of the hydrogel is high enough to minimize diffusional loss of the ferrocene derivative (or other AIM) components. Monomeric AIMs are generally not suitable for physical encapsulation because the high network density required to effectively retain them runs counter to the requirements of a highly swollen hydrogel. The exemplary ferrocene materials shown in Table 7 are suitable for such immobilization. Alternative hydrophilic scaffolds, including those based on sol-gel chemistry (see PCT Publication No. 2012 / 018632, incorporated herein by reference), may be used to immobilize AIM polymers or AIM hydrogels (or corresponding materials with ASMs for the preparation of WEs of the present invention) that have sufficiently high average molecular weights compared to the effective pore size of the scaffold to form IPNs and provide sufficient immobilization.
[0056] [Table 7]
[0057] Ferrocene (or other AIM) polymers can also be blended into other polymer matrices to obtain the AIM polymers and AIM hydrogels of the present invention. Such matrices are selected to impart certain attributes, such as thermal or chemical resistance, that exceed the performance envelope of the hydrogel. Polyvinylidene fluoride (PVDF), epoxies, electropolymerized polypyrrole, and various conductive ink formulations are exemplary materials that may be used for this purpose. These and other polymers may be used to meet the mechanical, dielectric, or biochemical requirements of application-specific sensors.
[0058] electrode design The present invention provides robust electrodes in which the AIM is not covalently bound to the substrate or the ASM is not covalently bound to the substrate, which may be the same or different. In some electrodes of the present invention, the AIM hydrogel is immobilized on the substrate surface by non-covalent means. The present invention provides substrates that enhance such binding, which have an appropriate level of surface texture, porosity, and / or three-dimensional tortuosity to ensure robust immobilization. These features can improve the binding and / or accommodation of the AIM hydrogel (or ASM hydrogel) without affecting the AIM's interaction with the analyte, due in part to the highly permeable nature of the swollen hydrogel. They also provide protection against physical damage associated with contact, abrasion, or detachment that may otherwise result from repeated swelling and shrinkage of the AIM hydrogel, compared to the same material disposed on a smooth surface such as glassy carbon or other metallic and non-metallic surfaces. Indeed, the mechanical properties of textured or porous substrates overcome the inherent fragility of the AIM hydrogel, resulting in high structural integrity.
[0059] Any conductive substrate can be used as an electrode to support, immobilize, and protect the AIM polymers and hydrogels (and ASM polymers and hydrogels) of the present invention. These can include carbon allotropes such as carbon fibers, porous graphite, macroporous carbon, mesoporous, microporous carbon, nanoporous carbon, carbon nanofibers (made by carbon coating materials such as nanoporous alumina) and composites thereof, and nanotubes and composites thereof. Metals can include nanoporous gold, platinum, and silver. Screen-printed electrodes can have a variety of surface coatings with desired roughness, including mesoporous carbon, carbon nanofibers, carbon nanotubes, graphene, or carbon inks imprinted with micro- or nanoscale features such as channels or pores. Porous conductive substrates also benefit from very short signal paths, thereby increasing signal capture efficiency.
[0060] Certain conductive polymers can be used as electrode substrates and coated with AIM hydrogel. Engineering polymer composites can be used as supports for AIM hydrogel, and the composites contain sufficient amounts of carbon allotropes or metal particles to make the composites conductive. Suitable polymers for such composites include epoxy, polysulfone, polyethersulfone, polyphenylene sulfide, polypyrrole, polyvinylidene fluoride, other fluoropolymers or copolymers, as well as various vinyl polymers, cellulosic polymers, and silicone polymers, such as PVC, polystyrene, polymethylmethacrylate, and their derivatives and copolymers.
[0061] The electrodes of the present invention may be fabricated using rigid substrates such as various carbon composites, or flexible conductive substrates (e.g., woven or nonwoven carbon fabrics), or nonconductive support films such as polyester, polyimide, polyolefin, etc., made conductive by conductive coatings (e.g., carbon ink, indium tin oxide, silver, etc.). The materials of the present invention may be formed in a variety of geometric patterns, complemented by closely spaced CE and PRE. For example, the electrodes may be arranged as concentric rings, segments, and arrays, as shown in FIG. 8. The conductive coatings and the electrodes derived therefrom allow sensors to be built in a wide range of form factors and dimensions.
[0062] 8, in some embodiments, the electrode components 1, 3, and 4 of the solid-state sensor are arranged as sections in a single concentric ring surrounding a central electrode 2. For example, in one embodiment, the sensing surface of the solid-state sensor includes a single concentric ring having multiple electrode segments, namely, an ASM-containing WE1, a pseudo reference electrode 3, and a counter electrode 4, arranged radially around a centrally located AIM-containing IE2. The sensing surface further includes a non-conductive material 5 interposed between the multiple electrodes. In some examples, the exposed surface areas of the various electrode segments are selected to generate a desired signal relative to one or more other electrode segments.
[0063] In some cases, the sensor material or composite is formed into a micro-hemisphere with a characteristic radius of approximately 25 micrometers or less. Sensors of these dimensions produce very low signals, but their reduced double-layer capacitance also shortens the response time. (See J. Wang, Analytical Chemistry, 3rd ed., 2006, John Wiley.) Sensor arrays can be constructed for use in miniature or microelectrodes with variable signal levels for practical applications.
[0064] In some examples, electrode components 1, 2, and 3 are provided as individual concentric rings surrounding a centrally located electrode component 4. A non-conductive material 5 is interposed between each of electrodes 1, 2, 3, and 4 to isolate the respective signals of each electrode component. In some examples, the location of the sensor component is selected based on the desired exposed surface area of the sensor component relative to one or more other electrode rings. In some examples, each concentric electrode ring has an equal width. In some examples, one or more concentric electrode rings has a unique width relative to one or more other electrode rings.
[0065] The conductive substrate may be further supported using robust support materials such as ceramic, glass, or fiberglass reinforced composites commonly used for printed circuit boards. These materials provide well-established connectivity options for transferring signals from the sensing element to the electrical circuit. Various mounting options (e.g., multi-layer printed circuit boards, through-plate contacts, etc.) provide increased packaging density, reliability, and functionality of sensors and devices.
[0066] AIM and ASM hydrogels may be applied to a substrate as a coating. However, in various embodiments, the AIM or ASM hydrogel is formed in situ to obtain a crosslinked structure. When applied as a coating, the AIM polymer (or ASM polymer) needs to be sufficiently soluble in a solvent or solvent mixture to prepare a coating solution, but sufficiently insoluble in the intended analyte (usually water) so that it remains on the electrode surface for the life of the sensor. This often limits the hydrophilicity of candidate linear AIM (or ASM) polymers. Crosslinking of the AIM (or ASM) polymer obviates this tradeoff, since even a low degree of crosslinking renders even highly hydrophilic polymers insoluble.
[0067] However, due to this insolubility, the cross-linked polymer cannot be applied as a solution but must be prepared in situ. This involves applying a solution of monomer and initiator to the substrate and then initiating the polymerization process. In this way, the monomer can penetrate into the pores of the substrate before polymerization and cross-linking. This ensures that the polymer adheres well to the substrate and conforms to any surface features and internal structures even in the absence of covalent linkage to the surface. Cross-linking is particularly beneficial for imparting dimensional stability and preserving a lower molecular weight fraction of the AIM (or ASM) hydrogel, which contributes to extending the functional life of the AIM sensor (IE) or ASM sensor (WE). Example 1 below illustrates this aspect of the invention by showing a method of making a ferrocene-containing electrode (IE) of the invention by producing a cross-linked hydrogel on the surface of an electrode, where the substrate is a carbon substrate.
[0068] The AIM and ASM hydrogels of the present invention exhibit good wet-dry reversibility, retaining their physical integrity when dried and rapidly restoring their redox activity and electrode potential upon rewetting.
[0069] A square wave voltammetry (SWV) method is used to generate signals from the sensor components of the present invention. The signals generated by the WE and IE can be monitored simultaneously or at different intervals. In the present context, the terms "sweep" and "scan" are used interchangeably. In embodiments where both the ASM and AIM are located on the same substrate, a square wave potential sweep is applied to elicit separate but simultaneous responses from the ASM and AIM. The same scan parameters (such as the range of the voltage sweep, the pedestal height, and the interval between scans, also referred to as dwell time) are applied at both electrodes.
[0070] In other embodiments where the ASM and AIM are located separately on separate, electrically independent electrodes and in accordance with the important new methodology provided by the present invention, two separate square wave potential sweeps with different scan parameters may be applied to the electrodes. Sampling the WE and IE separately provides several benefits. First, signal quality can be individually optimized for the ASM and AIM. Second, the IE can be sampled less frequently than the WE, and some AIMs are designed to remain unchanged in different analytes. Thus, the IE only needs to be sampled to reconfirm the quiescent state when a change in the analyte occurs or is expected. The time not spent sampling the IE can be used to resume monitoring the WE, which may actually shorten the WE dwell time and result in a more responsive pH measurement system. Third, sampling the IE less frequently allows the use of certain AIM materials that exhibit good accuracy and a wide pH insensitive range, but are susceptible to signal loss as a result of repeated electrochemical excitation.
[0071] In one embodiment, the SWV electronics of the sensor of the present invention is configured to multiplex between inputs from the WE and IE. The WE and IE inputs are electrically equivalent and share the reference electrode / pseudo reference electrode (RE / PRE) and CE circuitry. The operation of this system is illustrated in Table 8.
[0072] The discrimination mechanism of the potentiostat circuit (blocks 1-9) is a multiplexer (3), which is used to select either the ASM or AIM electrodes. Common to both the WE and IE are the impedance transamplifier (4), the analog-to-digital converter (ADC) (5), the reference electrode (6), the digital-to-analog converter (DAC) (7) to generate the square wave excitation, and the differential amplifier (8) that drives the counter electrode (9).
[0073] [Table 8]
[0074] SWV operating parameters, including voltage scan (or sweep) range, pedestal height, equilibration time, and dwell time (i.e., rest time between successive voltage scans), are independently adjustable for the WE and IE. In one embodiment, the same SWV circuitry is used to continuously monitor the WE and IE.
[0075] The complete time series of WE and IE scans is shown in Table 9. Arrows represent groups or repetitions of scans occurring at regular intervals set with independent dwell times.
[0076] [Table 9]
[0077] Scan parameters are optimized for each electrode. Statistics, i.e., peak potential averages and standard deviations of a series of scan repetitions, are kept separately for WE and IE, allowing results from these electrodes to be analyzed independently.
[0078] Operating parameters for the SWV for the WE and IE of the present invention, including typical ranges and preferred values, are shown in Table 10.
[0079] [Table 10]
[0080] A special feature of the SWV technique of the present invention is the implementation of two operating modes. First, a "search" mode is used at the beginning of each voltage scan, which covers a relatively wide potential range to determine the location of the ASM or AIM peak potential in the analyte. Second, a "track" mode is used with smaller voltage increments to determine the location of the peak potential from the electrode with higher resolution. In the track mode, for example, a step height of 2 mV corresponds to a pH resolution of 0.03 pH units. This is sufficient for most pH analysis applications. It is possible to further reduce the step height to 1 mV (for a resolution of 0.015 pH units), but doing so would also increase the time required to span the ±200 mV range. A narrower scan width is sufficient to ensure that most of the AIM peak potentials remain unchanged.
[0081] The following procedure describes how the signals from the WE and IE are used to derive the concentration of the analyte of interest, in this case the hydronium ion concentration expressed in terms of pH.
[0082] As shown in Tables 11-13, the start of the scan (1) begins with a wide SWV sweep (2a) of the WE at low resolution to search for the subsequent WE tracking scan (2b). The sweep speed is set by the step height (SH) of each voltage increment between the limits of the voltage range. The processing of the SWV output to find the peak is summarized in steps 3-6. Immediately after the WE search scan (2a) and before the start of the WE tracking scan (2b), a wide SWV sweep (8a) of the IE searches for the center of the subsequent IE tracking scan. The first group of IE tracking scans is averaged to determine the AIM baseline (9) and stored in non-volatile memory (10). The difference (steps 3-6) of the peak of the subsequent AIM tracking scan (8b) from the AIM baseline is equal to ΔAIM (11). Since the AIM peak is invariant, ΔAIM reflects the drift of the RE or PRE. The ASM peak is corrected by ΔAIM (7), applied as a correction factor equivalent to the drift of the RE or PRE. The calibration table characterizes the average ASM response to standard buffers over a range of pH (e.g., pH 2 to pH 12) at several temperatures (e.g., 5°C to 50°C). Entries into the calibration table are made under controlled conditions using a stable RE such as Ag / AgCl or mercurous chloride. From the calibration table, the corresponding pH of the sample is determined (12) at a sensor temperature and voltage equal to the corrected ASM (7).
[0083] [Table 11]
[0084] [Table 12]
[0085] [Table 13]
[0086] Determination of pH (or other analyte concentration) with the WE-IE pair of the present invention can be performed as follows: A calibration table of the response of the ASM to pH buffers over a temperature range referenced to a standard Ag / AgCl or mercuric chloride reference electrode can be used, allowing the ASM peak to be corrected in response to drift in the AIM. An alternative method is to prepare the calibration table directly from the difference between the ASM and AIM peak potentials to pH buffers over a given temperature range. These operations can be built into the firmware of the analyte sensing device of the present invention.
[0087] The analyte sensing device of the present invention comprises a sensor assembly comprising at least one each of a WE, an IE, a RE (CRE or PRE, but typically a PRE), and a CE. These sensor components may be configured in a variety of spatial arrangements, surface area ratios, planar or three-dimensional designs, coaxial or non-coaxial geometries, or any combination thereof.
[0088] One desirable configuration provided by the present invention is a 12 mm diameter sensor assembly. This geometry is similar to conventional glass electrodes, making it compatible with instruments and equipment. The sensing elements of the present invention can be co-located at the end plane of the 12 mm diameter probe, or can be suitably embedded for protection, or structured in a three-dimensional space accessible to the analyte. The counter electrode can be one of the components co-located on the end surface, as shown in FIG. 8, or can be in the form of a ring or circular line surrounding the other sensing element.
[0089] Another embodiment provided by the present invention is a multi-well or micro-well plate in which there is an addressable sensor on the bottom and / or inside wall of every well, as shown in FIG. 9. The configuration of the electrodes is, in some embodiments, similar to the 12 mm probe design described above. The main difference is the size of the electrode surface and the electronics interface. In the case of a multi-well plate, the electrical connection to each electrode can be achieved through holes to the back of the plate or by conductive wires. These connections are common in multi-well plate sensors for monitoring electrical conductivity. In a typical configuration, a 96-well plate will contain 50-200 microliters of solution per well. The electrode surface on the bottom of each well will be approximately 1-2 square millimeters, with a well diameter of about 1 cm. Various exemplary embodiments of the sensor design are shown in FIG. 8. In alternative embodiments, electrodes may be incorporated into the multi-well plate such that the analyte contacts all the sensing elements to enable measurements. In certain embodiments, one or more electrodes are located on the walls of the sample cavity, making at least a portion, if not all, of the bottom transparent for optical analysis. Alternatively, printed electrodes located on flexible films are particularly suitable as components in flexible containers, tubing sets, and other components for bioprocessing, including single-use or disposable components.
[0090] Referring now to FIG. 10, the present invention is also applicable to pH measurements in very small analyte sample volumes, in particular according to PCT Publication No. 2014 / 106066, which is incorporated herein by reference. This embodiment includes a sensor assembly and derived meter for measuring droplets of liquid on the order of microliters or sub-microliters. In this embodiment, the WE, IE, and PRE are all located on an area of the order of a few square millimeters. In one embodiment, this is a WE / IE module. The proximity ensures that the WE / IE module and the RE contact the sample at the same time. The circuit is completed when the CE module with a similarly sized CE comes in close proximity to the WE component. The gap formed between these sensor components is used to hold the analyte droplet by capillary action, bridging and wetting the electrode surfaces, completing the electrochemical circuit. Current flows only when the sample droplet bridges the two parts of the sensing assembly.
[0091] Various aspects of the invention are also illustrated in the following examples. EXAMPLES
[0092] Example 1: Ferrocene-containing electrodes produced by forming a cross-linked hydrogel on the electrode surface. In this example, the AIM hydrogel of the present invention is immobilized (not covalently attached) to the electrode surface during the polymerization process used to form the hydrogel. After polymerization, the electrode is washed in water or a water-solvent mixture to remove contaminants, unreacted monomers, and reaction by-products. Excess hydrogel is removed from the electrode surface. The electrode is then placed in a housing where the hydrogel-containing surface is exposed to the analyte solution. The conductive backside of the substrate is connected to a potentiostat. The AIM signal is acquired by applying a sweeping square wave potential against a reference or pseudo reference electrode to give a current peak. The current peak potential from the AIM is then used to correct for drift of the reference electrode or as a reference for a separate working electrode (ASM).
[0093] In this example, the chemical structure of the AIM comprises ferrocene covalently bonded to a hydrophilic cross-linked polymer matrix of the present invention. The electrodes are produced by polymerizing a monomer mixture in the presence of a conductive substrate. A monomer solution containing 5 wt% polyethylene glycol (PEG) diacrylate and N,N-dimethylacrylamide (DMMA) with 1 wt% vinylferrocene was diluted in n-butanol to obtain a 25% solution. A heat-activated initiator (azobisisobutyronitrile, AIBN) was added to a concentration of 0.5 w / v%. A carbon fiber electrode disk was immersed in the mixture, which was then sonicated and sparged with argon to remove oxygen. The mixture was capped and heated at 60°C for 24 hours to produce a hydrogel of the present invention. The electrodes were cut from the gel and washed in fresh water for 2 days. Excess hydrogel was then removed from the electrode surface. The electrodes were stored in water until use.
[0094] Alternatively, the electrodes are produced by polymerizing the monomer mixture in the presence of a conductive substrate. In this case, a monomer solution containing 3 wt% N,N'-methylenebisacrylamide and N,N-dimethylacrylamide (DMMA) with 3 wt% vinylferrocene was diluted in n-butanol to obtain a solution. A thermally activated initiator (e.g., azobisisobutyronitrile, AIBN) was added to a concentration of 0.5 w / v%. A carbon fiber electrode disk was immersed in the mixture, which was then sonicated and sparged with argon to remove oxygen. The mixture was capped and heated at 75°C. Gelation occurred in 20-60 minutes to produce the hydrogel of the present invention. After 90 minutes, the electrode was cut from the gel and allowed to swell in alcohol for 12-18 hours, after which the electrode was washed in 1:1 alcohol:water for 2 hours followed by DI water for 2 hours. Excess hydrogel was then removed from the electrode surface. The electrode was then stored in water until use.
[0095] Referring now to FIG. 3, four solid-state sensor components were deployed by co-immersion in a given analyte solution. The IE was prepared by in-situ polymerization of ferrocene-hydrogel onto a carbon fiber substrate. The WE utilized polyvinyl alcohol anthraquinone (PVA-AQ) prepared as described in US Patent Publication No. 20130168609, which is incorporated herein by reference. An alternative chemical structure for PVA-AQ according to the present invention is provided below in Example 4. The counter electrode CE was a stainless steel ring surrounding the WE. All voltammetric measurements were performed against a pseudo reference electrode (PRE), which in this case was a silver / silver chloride film screen printed onto a flexible polyester substrate. The WE shown in FIG. 3 was constructed using an improvised method using bases such as n-butyl lithium, sodium hydride, or potassium tert-butoxide.
[0096] To confirm the pH insensitive range of the AIM hydrogel, three IEs were prepared and tested against a standard calomel electrode (SCE) in a series of buffer solutions, each containing 100 mM added sodium chloride. Square wave voltammetry peak values were obtained from five measurements. An ideal AIM would show no deviation in peak potential regardless of pH. As shown in Table 14 below, the tested IEs (EL1, EL2, EL3) show stability across the pH scale of different sensitivity. In the biorelevant range of pH 7.5-6, there was a maximum deviation of 2 mV. Over a wider range the deviation is larger, with the electrodes showing a standard deviation of 2 or 3 mV for the range of pH 2-pH 10. This error, considering the slope of 58 mV / pH unit for the ASM, will determine the resolution achievable using the AIM for a given pH range. For example, an error of 6 mV means a pH measurement error of 0.1 units.
[0097] [Table 14]
[0098] The AIM hydrogel used to generate the results in Table 1 was a matrix of DMAA crosslinked with 5% PEG-diacrylate and containing 1 wt% vinylferrocene. EL1 and EL2 were polymerized at 20 wt% solids in the gel, and EL3 was polymerized at 25% solids in the gel. The electrodes were SWV scanned five times in each buffer with a 90 second delay between scans. The values reported in Table 1 are the last measurements in the five scan series. The values in Table 1 for the pH 7 buffer are the average of measurements taken at the beginning and end of the pH excursion.
[0099] The characteristic responses of WE and IE to pH changes are shown in Figure 4. Within experimental error, the AIM peaks measured in buffers at pH 6, 7, and 8 overlapped, whereas the ASM peaks showed the expected changes as a function of pH.
[0100] The effect of changing the reference electrode on the WE-IE couple is shown in Figure 5. In this case, a pH 6 buffer was used. For the PRE-displayed data (solid line), the solid Ag / AgCl PRE shown in Figure 3 was used. The ASM peak (left) and AIM peak (right) were 675 mV apart. For the liquid-junction RE-displayed data (dashed line), a commercial Ag / AgCl reference electrode was used instead. The ASM and AIM peaks were 671 mV apart. Despite a nearly 100 mV shift in the reference potential, the difference between the AIM and ASM peaks was nearly identical. Thus, these results indicate that the AIM-ASM relationship is independent of RE for this WE-IE couple of the present invention.
[0101] Example 2: Intrinsic pH response of an all-solid-state pH sensor system In conventional SWV, pH correlates directly with the characteristic potential of a single WE. For WE-IE pairs, the difference in the potential of these two electrodes correlates with pH. In this example, two WE-IE pairs were deployed with a counter electrode made of a thin stainless steel rod and a screen-printed silver / silver chloride electrode serving as the PRE. All sensor components were solid-state. As noted above, the nature of the reference electrode is somewhat flexible, and the pH calibration curve only takes into account the difference between the AIM and ASM peak positions. In this case, calibrations were generated for duplicate WE-IE pairs using 20 mM buffer and 100 mM sodium chloride at ambient temperature (22-24 °C). The results are shown in Figure 6.
[0102] Figure 6 shows the linear relationship between potential and pH for two separate WE-IE pairs. The potential in this case is the difference between the AIM and ASM peaks measured against the PRE. This can be considered a calibration curve, and the slope and intercept can be used to determine the pH of an unknown. Ideally, the ASM-AIM potential difference depends only on the pH, not the absolute potential of the PRE.
[0103] Example 3: Response of WE-IE pairs to analyte perturbations, e.g., ionic strength It is generally recognized that the reference electrode potential can be affected by changes in analyte ionic strength. These changes can be compensated for by calibration at the expected ionic strength in conventional potentiometric pH measurements. In the WE-IE electrode pair of the present invention, changes in the RE (typically the PRE) potential affect the ASM and AIM in the same way. Thus, the errors are automatically cancelled. This effect is shown in FIG. 7, where the ASM-AIM pair is compared to a conventional glass pH electrode (Thermo Orion). The WE-IE pair was first calibrated in a BDH reference standard buffer (VWR International) containing 100 mM added salt (sodium chloride). Subsequent measurements in a 10 mM sodium chloride solution shifted the PRE potential by 30 mV. The pH measured with the calibrated glass pH probe is indicated using open circles. The pH measured using the WE on the Ag / AgCl PRE without any calibration is marked with an X. The error is due to the shift in the PRE. The AIM calibrated pH is indicated with a filled circle. The accuracy of the calibrated pH values indicates that the AIM is much less sensitive to ionic strength compared to the PRE. In summary, these results show that the WE-IE pair of the present invention compensates for the effect of ionic strength on the CRE or PRE.
[0104] Example 4: PVA-AQ (ASM) Chemistry Electrodes suitable for use in the pH meter of the present invention can be prepared from a hydrogel consisting of polyvinyl alcohol covalently bonded to an anthraquinone derivative (PVA-AQ). PVA-AQ was synthesized using diethylaminomethyl polystyrene: a base for polymers commonly used in organic synthesis reactions. This reaction generally requires about 48 hours to complete. To shorten the reaction time, the present invention provides a method to react n-butyl lithium, sodium hydride, and potassium tert-butoxide, but any of a number of bases commonly used in organic synthesis reactions may be substituted, and the reaction conditions modified as necessary to produce the desired PVA-AQ of the present invention, including any substitution to vary the reaction time and / or density of AQ functionalization. Thus, the method and PVA-AQ chemistry of the present invention may be tailored by using several different bases to achieve the functionalization of PVA desired for a particular application. An exemplary synthesis of PVA-AQ using n-butyl lithium as the base is shown in Table 15.
[0105] [Table 15]
[0106] Synthesis of PVA-AQ using n-butyllithium as a base The procedure for preparing the PVA-AQ ASM in Table 14 is as follows: An oven-dried 500 ml flask with a stir bar was purged with argon for 30 minutes. 1.77 g (0.042 moles) of PVA was added to the flask along with 300 mL of dry DMSO via cannula transfer. The system was maintained under positive argon pressure and heated to 50° C. in an oil bath with magnetic stirring to dissolve the PVA. After 2 hours, the flask was cooled to room temperature and 10.4 mL (0.0166 moles) of n-butyllithium was added. After 15 minutes, 5 g of 2-bromomethylanthraquinone was added. This was allowed to stir under argon at ambient temperature for 20 hours. The next day, the cloudy brown crude reaction mixture was added dropwise into 10 volumes of stirred 1,4-dioxane. The resulting solution is caramel brown with pale yellow solids. The solution was allowed to stir for 2 hours and then vacuum filtered on a fritted glass Buchner funnel. Alternatively, the mixture may be allowed to settle and a pale yellow solid may be isolated after removing the solvent mixture by decantation. The solid was washed with acetone. The solid was again dissolved in DMSO and precipitated with 1,4-dioxane and acetone to remove any unreacted bromomethylanthraquinone. A hexane wash was also used to help remove impurities.
[0107] B. Synthesis of PVA-AQ using sodium hydride as a base An oven-dried round-bottom flask with a stir bar (flask 1) was left under argon for 30 minutes. 924 mg (21 mmol) of PVA was added to the flask along with 50 ml of dry DMF was added via cannula transfer. An oil bath was heated to 120° C. and the flask was placed in the oil bath to dissolve the PVA. Once the PVA was dissolved, the flask was removed from the oil bath and allowed to cool to room temperature. 20 ml of dry DMF was added via cannula transfer to a second oven-dried flask (flask 2). Sodium hydride (400 mg, 10 mmol) was added to flask 2 and stirred. The contents of flask 2 were added to flask 1 via cannula transfer. The sodium hydride / PVA mixture in flask 1 appeared as a pale yellow suspension. After stirring for 20 minutes, bromomethylanthraquinone (300 mg, 1 mmol) was added to the reaction. After 5 minutes, the mixture was a deep tan color with very little undissolved solid. The mixture was stirred for 90 minutes. 0.5 mL of water was added to quench the reaction and then stirred for an additional 30 minutes. 10.5 mL (10.5 mmol) of 1 M hydrochloric acid was then added to flask 1 to neutralize the deprotonated PVA and help solubilize the mixture, which turned pale yellow. The contents of flask 1 were added dropwise into a new flask (flask 3) containing 1.5 L of acetone and stirred for 15 minutes during which a pale yellow precipitate formed. The precipitate was allowed to settle for 10 minutes and then decanted to reduce the volume of the precipitate. The decanted precipitate was then vacuum filtered over an ice bath. The solid was then washed with acetone and dried under vacuum.
[0108] Example 5: Preparation of Carbon Fiber Discs The target sensing surface of a carbon fiber / polyvinyl ester disk (8.5 mm diameter) was rubbed with 220 grit sandpaper. The rubbed disk was then placed in a 100 ml beaker to which 50 ml of hexane (VWR) was then added along with 1 minute of sonication. The excess hexane was removed from the beaker. 50 ml of ethanol (VWR) was added to the beaker and sonication continued for 1 minute, after which the excess ethanol was removed. A third cleaning step was completed by again adding 50 ml of ethanol to the beaker and sonicating the disk for 1 minute, after which the excess ethanol was removed. The cleaned disk was then stored dry until use.
[0109] Example 6: Pregel Mixture I 0.06 g of vinylferrocene, 0.06 g of bisacrylamide, and 1.88 g of DMAA were added to a clean vial to obtain 2 g of hydrogel monomer solution. The contents of the vial were mixed to dissolve the vinylferrocene. Prior to storage, the headspace of the vial was purged with dry argon gas by gently flowing a stream of argon into the vial for 10 seconds. A cap was then placed on the vial and the vial was stored in a freezer (-18 to -22 °C) for up to one week.
[0110] Example 7: Pregel Mixture II 0.10 g of vinylferrocene, 1.0 g of poly(ethylene glycol) diacrylate, and 8.9 g of DMAA were added to a clean vial to obtain 10 g of hydrogel monomer solution. The contents of the vial were mixed to dissolve the vinylferrocene. Prior to storage, the headspace of the vial was purged with dry argon gas by gently flowing a stream of argon into the vial for 10 seconds. A cap was then placed on the vial and the vial was stored in a freezer (-18 to -22 °C) for up to one week.
[0111] Example 8: In-situ formation of hydrogels with carbon fiber electrodes An oil bath was preheated and equilibrated at 75°C (+ / - 2°C) with stirring at a speed of 50-100 rpm using a wide stir bar. 20 mg of AIBN, 0.75 ml of monomer solution, and 3.0 ml of n-butanol were added to a 20 ml vial and mixed to dissolve the AIBN. Scrubbed and cleaned carbon fiber disks were stacked and added, rubbed side up, to the bottom of the vial. A micro stir bar was added to the vial on top of the disks. The vial was then sonicated for 10 seconds. The solution in the vial was then sparged with argon for 1 minute using a stainless steel hollow needle and mixed by gentle swirling at 20 second intervals. The vial was then tightly capped and immersed in the oil bath such that the liquid contents of the vial were 1 cm below the oil level. While in the oil bath, the liquid contents of the vial were mixed with a micro stir bar at a speed of approximately 50-100 rpm to gently agitate the solution without dislodging the carbon fiber disk. Gelation occurred after approximately 20 and 60 minutes in the oil bath and is visualized by immobilization of the micro stir bar. After a total of 90 minutes in the oil bath, the vial was removed and allowed to cool to ambient temperature.
[0112] Example 9: Cleaning and storage of hydrogel electrodes Use a metal spatula to break up the hydrogel solution so that the carbon fiber disc can be released. 15 ml of ethanol (95%) is added to the vial containing the carbon fiber disc, and then the vial is stirred and mixed for 12-18 hours to allow the hydrogel solution to swell. The excess ethanol and swollen hydrogel are then removed from the vial. 15 ml of an ethanol / water solution (1:1) is added to the disc in the vial and stirred for 2 hours, after which the excess solution is removed from the vial. 15 ml of water is then added to the disc in the vial and stirred for an additional 2 hours.
[0113] Excess hydrogel is removed from the surface of each electrode by gently scraping both over the surface and the edges using a razor blade. The electrodes are then dried on paper (Kimwipe) for 10 minutes. The electrodes are then transferred to clean, labeled screw-cap vials.
[0114] Example 10: Preparation of Ferrocene / PVA Acetal Using Ferrocene Carboxaldehyde Referring to Table 16, polyvinyl alcohol (2.0 gm, 4.55 x 10 -2 eq.) was dissolved in 1-methyl-2-pyrrolidinone (NMP, 50 mL) by stirring overnight at room temperature. Then, ferrocene carboxaldehyde (500 mg, 2.34×10 -3 (mol) was added to this stirred solution. Concentrated hydrochloric acid (1.0 mL) was then added and the resulting solution was stirred at room temperature for 48 h. The polymer was precipitated by slow addition of the NMP solution to vigorously stirred ethyl acetate (250 mL). After addition was complete, the ethyl acetate was decanted from the polymer, which was then stirred twice in ethyl acetate (250 mL each) to remove residual NMP and unbound ferrocene carboxaldehyde. The polymer was isolated by filtration, washed with ethyl acetate and then dried under vacuum.
[0115] [Table 16]
[0116] Example 11: Ferrocene / PVA acetal hydrogel formation on carbon fiber materials SEN-01-46b is applied to the prepared carbon fiber discs as a solution and subsequently dried and cured to become insoluble.
[0117] Alternatively, the SEN-01-46b solution is first mixed with a pure PVA solution to adjust the molar % concentration of ferrocene. The adjusted SEN-01-46b solution is then applied to the prepared carbon fiber disk. A crosslinker selected from the group consisting of maleic anhydride, maleic acid, glutaraldehyde, diisocyanate, divinyl ether, periodate, or any common dialdehyde is then added to the solution to promote the formation of a hydrogel on the prepared carbon material.
Claims
[Claim 1] 1. A method for measuring an analyte using an analyte sensor, comprising: the analyte sensor comprises a first working electrode (WE), an indicator electrode (IE), a counter electrode, a reference electrode (RE), means for applying a square wave potential sweep between a first pair and a second pair of electrodes, and means for detecting a relative shift between a first peak and a second peak in a square wave voltammogram; the first working electrode (WE) comprises a first set of redox species, the first set of redox species comprising one or more redox species sensitive to the analyte; the indicator electrode (IE) comprises a second set of redox species, the second set of redox species comprising one or more redox species that are insensitive to the analyte; the first pair of electrodes comprises the first working electrode (WE) and the reference electrode (RE), and the second pair of electrodes comprises the indicator electrode (IE) and the reference electrode (RE); the first peak is generated by one of an oxidation and a reduction of the first set of redox species, and the second peak is generated by one of an oxidation and a reduction of the second set of redox species; The method uses an indicator electrode (IE) in which at least the second set of redox species are not covalently bound to a surface of the indicator electrode (IE) but are instead encapsulated in a polymeric material bound to the surface of the indicator electrode (IE) by covalent or non-covalent bonds, or both.
Citation Information
Patent Citations
Device for detecting analytes
JP2012522223A
Analytical sensor
JP2013537627A
Analytical sample sensor
JP2015510116A
Electro-chemical sensor
US20080023328A1
Electrochemical sensor
US20120132544A1